2014
DOI: 10.15193/zntj/2014/96/053-062
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Meat From Young Bulls of 3 Native Breeds: Polish Red, White-Backed, and Polish Black-and-White, as Well as of Simmental and Polish Holstein-Fresian Breeds

Abstract: ZYGMUNT LITWIŃCZUK, MARIUSZ FLOREK, PIOTR DOMARADZKI, PAWEŁ ŻÓŁKIEWSKI  WŁAŚCIWOŚCI FIZYKOCHEMICZNE MIĘSA BUHAJKÓW TRZECH RODZIMYCH RAS -POLSKIEJ CZERWONEJ, BIAŁOGRZBIETEJ I POLSKIEJ CZARNO-BIAŁEJ ORAZ SIMENTALSKIEJ I POLSKIEJ HOLSZTYŃSKO-FRYZYJSKIEJS t r e s z c z e n i e Celem badań była ocena właściwości fizykochemicznych mięsa buhajków trzech rodzimych ras: polskiej czerwonej (PC), białogrzbietej (BG) i polskiej czarno-białej (PCB) i ich porównanie z cechami mięsa buhajków ras: simentalskiej (SIM) i polsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
0
2
Order By: Relevance
“…The average daily weight gains of calves obtained in the present study, amounting to 880 g, were higher than those reported by Litwińczuk et al [54] (730 g). It should be noted that the calves in the present study were kept with their mothers in the pasture, while in the study by Litwińczuk et al [54] the animals were kept indoors without their mothers.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The average daily weight gains of calves obtained in the present study, amounting to 880 g, were higher than those reported by Litwińczuk et al [54] (730 g). It should be noted that the calves in the present study were kept with their mothers in the pasture, while in the study by Litwińczuk et al [54] the animals were kept indoors without their mothers.…”
Section: Discussioncontrasting
confidence: 83%
“…The average daily weight gains of calves obtained in the present study, amounting to 880 g, were higher than those reported by Litwińczuk et al [54] (730 g). It should be noted that the calves in the present study were kept with their mothers in the pasture, while in the study by Litwińczuk et al [54] the animals were kept indoors without their mothers. Similar daily gains (850 g for heifers) or somewhat higher values (1120 g in bullocks) than in the present study were reported by Choroszy and Choroszy [55] for feedlot calves up to 12 months of age.…”
Section: Discussioncontrasting
confidence: 83%
“…In addition to the rare coat colour (side colouring) of the Polish White-Backed breed, research by Barłowska et al [11] and Litwi ńczuk et al [12] has shown that their milk has favourable physical and chemical characteristics, especially for processing. Similar conclusions were drawn from an analysis of the physical and chemical properties of the meat of Polish White-Backed cattle [13]. Their high fattening capacity has been observed in particular on semi-intensive farms using on-farm feed from permanent grassland [14].…”
Section: Introductionsupporting
confidence: 75%